Enhancing Muhadatsah Skills Through Structured Question Cards in Arabic Language Learning - Herdah Herdah; Raodhatul Jannah; Rara Mutiah; Rahmatika Rahmatika (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2026)
This study aims to evaluate the effectiveness of structured question cards in improving the muhadatsah (Arabic speaking) skills of students in the Arabic Language Education Study Program at IAIN Parepare. The research was motivated by the limited fluency and coherence observed in students’ oral production, indicating the need for an instructional medium that provides systematic scaffolding. A quasi-experimental design employing a pre-test and post-test without a control group was used, involving 20 students as participants. In addition to oral tests, data were collected through classroom observations across four treatment sessions and interviews to examine supporting and inhibiting factors throughout the learning process. Results revealed a significant improvement in students’ speaking skills, with mean scores rising from 64.3 to 82.7, representing a 28.6% increase. A t-test value of 9.84, which exceeded the critical value at the 0.05 significance level, confirmed the significant impact of the media on muhadatsah development. The study also found that a supportive classroom environment, systematically designed cards, and collaborative practice served as major facilitating factors, whereas variations in initial ability and limited class time posed challenges. These findings suggest that structured question cards constitute an effective and practical instructional medium for enhancing learners’ oral communicative performance in Arabic language education.